Students’s Misconceptions Of Social Arithmetic Problems - Wati, Cut Mirna; Zulmaulida, Rahmy; Akmal, Nurul (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2023)
The purpose of this study was to determine the analysis of misconceptions of social arithmetic material in grade VII students at SMP Negeri 1 Simpang Keuramat. The research approach used in this study is a descriptive qualitative method. The research was conducted at SMP Negeri 1 Simpang Keuramat class VII. The subjects of the study were students of class VII-1 totaling 13 students. Data analysis techniques are qualitative analysis, namely data collection, data reduction, data presentation and drawing conclusions. The data collection instruments used in this study are test instruments, namely misconception tests and non-test instruments, interview guidelines. The results of the study found several misconceptions experienced by students in social arithmetic material categorized into five types, namely students who experienced concept misconceptions as many as 1 person with a percentage of 7.69%, students who experienced numeracy misconceptions as many as 2 people with a percentage of 15.3%, students who experienced systematic misconceptions as many as 6 people with a percentage of 46.1%, students who experienced misconceptions as many as 3 people with a percentage of 23%, students who experienced misconceptions of strategies were 5 people with a percentage of 38.5%.